KONSTRUKSI SOSIAL ATLET DISABILITAS ASEAN PARA GAMES 2022 DI MEDIA ONLINE - Elfa Dhiotami, Adeillia; Hasfi, Nurul; Nugroho, Adi (Interaksi Online, 2024)
Indonesia, which was chosen to host the 2022 ASEAN Para Games, was in the spotlight of online media Okezone.com and Solopos.com which published news about athletes with disabilities competing in this event. Because of this, the news of athletes with disabilities is considered that there are still stereotypes attached to the news of athletes with disabilities and news writing that still uses figures of speech to corner the physical condition of the athletes. This study aims to analyze the news frames created by Okezone.com and Solopos.com on athletes with disabilities competing in the 2022 ASEAN Para Games with social construction theory by Peter L. Berger and Thomas Luckmann. The framing model used in this research is the framing model of William A. Gamson and Modigliani which focuses on how to tell a story or a group of ideas that present meaning construction. This research uses a qualitative method with a sample of 9 news from Okezone.com and 3 news from Solopos.com from February 2022 to August 2022. Based on the framing model of William A. Gamson and Modigliani which uses two devices, framing devices and reasoning devices, the results of the study found that athletes with disabilities were framed from 5 themes, namely (1) Athletes with disabilities as heroes, (2) Athletes with disabilities as passive victims, (3) Athletes with disabilities as objects of interest, (4) Athletes with disabilities as objects of public curiosity, (5) Disabled athletes as self-defeating individuals. This is shown from how Okezone.com and Solopos.com highlight the achievements of ASEAN Para Games disabled athletes so as to form a construction that people with disabilities are considered to have obtained their rights fairly but at the same time form an unbalanced standard against other people with disabilities who do not have abilities in sports.